Presence of the peculiar carnivore Sivanasua in Carinthia. (3rd August 2022) - Prieto, Jérôme; Gross, Martin; Hassler, Andreas; Böhme, Madelaine
ABSTRACT: A lophocyonid carnivore (Mammalia) is reported for the first time from Miocene (lower Badenian, ca. 16 My) deposits in Austria. A single, lower first molar from Schönweg-"Brüchl" (Lavanttal, Carinthia) is assigned to Sivanasua viverroides . The species is also recognised in Germany in few faunas of similar ages.